A long way from New York City: Socially stratified contact-induced phonological convergence in Ganluo Ersu (Sichuan, China). (22nd May 2018) - Chirkova, Katia; Stanford, James N.; Wang, Dehe
Abstract: Labov's classic study, The Social Stratification of English in New York City (1966), paved the way for generations of researchers to examine sociolinguistic patterns in many different communities (Bell, Sharma, & Britain, 2016). This research paradigm has traditionally tended to focus on Western industrialized communities and large world languages and dialects, leaving many unanswered questions about lesser-studied indigenous minority communities. In this study, we examine whether Labovian models for age, sex, and social stratification (Labov, 1966, 2001; Trudgill, 1972, 1974) may be effectively applied to a small, endangered Tibeto-Burman language in southwestern China: Ganluo Ersu. Using new field recordings with 97 speakers, we find evidence of phonological change in progress as Ganluo Ersu consonants are converging toward Chinese phonology. The results suggest that when an endangered language undergoes convergence toward a majority language due to intense contact, this convergence is manifested in a socially stratified way that is consistent with many of the predictions of the classic Labovian sociolinguistic principles.